2021
DOI: 10.1002/alr.22780
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dupilumab in patients with a history of prior sinus surgery for chronic rhinosinusitis with nasal polyps

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is a type 2 inflammatory disease treated with sinus surgery when refractory to medical intervention. However, recurrence postsurgery is common. Dupilumab, a fully human monoclonal antibody, blocks the shared receptor for interleukin 4 (IL‐4) and IL‐13, key and central drivers of type 2 inflammation. We report the efficacy of dupilumab in patients with CRSwNP from the SINUS‐24/SINUS‐52 trials (NCT02912468/NCT02898454), by number of prior surgeries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 40 publications
0
51
2
Order By: Relevance
“…The biologics dupilumab (63)(64)(65), omalizumab (66,67), and mepolizumab (68) have been shown to improve olfaction based on symptom scores and olfaction tests. Dupilumab, blocking the shared receptor component of IL-4 and IL-13, can even improve olfaction function in patients who previously underwent more than 3 surgeries (69,70). Successful treatment with biologics may imply that type 2 inflammation plays a role in the disease mechanism of olfactory dysfunction in CRS.…”
Section: Treatment Of Olfactory Dysfunction In Chronic Rhinosinusitismentioning
confidence: 99%
“…The biologics dupilumab (63)(64)(65), omalizumab (66,67), and mepolizumab (68) have been shown to improve olfaction based on symptom scores and olfaction tests. Dupilumab, blocking the shared receptor component of IL-4 and IL-13, can even improve olfaction function in patients who previously underwent more than 3 surgeries (69,70). Successful treatment with biologics may imply that type 2 inflammation plays a role in the disease mechanism of olfactory dysfunction in CRS.…”
Section: Treatment Of Olfactory Dysfunction In Chronic Rhinosinusitismentioning
confidence: 99%
“…N-ERD is associated with significantly higher risk of revision surgery (33) , research suggests that patients with N-ERD achieve greater improvements in nasal congestion, total symptom scores, radiological severity and SNOT-22 scores than those without. Patients with a history of previous surgery, particularly those that have a symptomatic recurrence that requires revision within 3 years, are at a higher risk of undergoing further surgical intervention (33) ; again a recent study has shown that while all groups benefit from dupilumab, those with a history of increasing numbers of previous surgery, or reducing time since last surgery to revision benefit the most (34) . It appears that characte-…”
Section: Justicementioning
confidence: 99%
“…With the development of the biological treatments (45)(46)(47) , it is very likely from initial investigations that olfactory function can be further improved (48) without the need of recurrent systemic steroids. However more real-life studies in this field are needed to draw a more comprehensive picture of when and which biological treatment is best used for patients with treatment-refractory olfactory dysfunction (49,50) .…”
Section: Not All Smell Disorders Are Covid-19mentioning
confidence: 99%